An unusual swelling in the male perineum. (22nd January 2015) - Parnham, Arie Stewart; Freeman, Alex; Kirkham, Alex; Muneer, Asif
Abstract : Median raphe cysts are a rare, congenital entity. We present a case and review the literature in respect to a 35-year-old man with a non-visible, painless midline swelling in the anterior perineum initially thought to be a liposarcoma. Subsequent histopathological examination confirmed a median raphe cyst.